2018
DOI: 10.1007/s11051-018-4214-6
|View full text |Cite
|
Sign up to set email alerts
|

Collective magnetic response of inhomogeneous nanoisland FeNi films around the percolation transition

Abstract: By using superconducting quantum interference device (SQUID) magnetometry we investigated anisotropic high-field (H 7 T) low-temperature (10 K) magnetization response of inhomogeneous nanoisland FeNi films grown by rf sputtering deposition on Sitall (TiO2) glass substrates. In the grown FeNi films, the FeNi layer nominal thickness varied from 0.6 to 2.5 nm, across the percolation transition at the dc ≃ 1.8 nm. We discovered that, beyond conventional spin-magnetism of Fe21Ni79 permalloy, the extracted out-of-pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 43 publications
(48 reference statements)
0
14
0
Order By: Relevance
“…Another paradigm is represented by the MLF sample N1, where the 0.52-nm thick FeNi layer is far from the percolation transition and the FeNi layers are well separated from each other (by 4.6 nm). Earlier, we established that ultrathin monolayers of FeNi nanoislands exhibit superparamagnetic-like (SPM) behaviour at room temperature, associated with their giant magnetic moments of 10 3 -10 5 µ B 36,40 . In the MLF sample N1, incorporating www.nature.com/scientificreports/ www.nature.com/scientificreports/ such FeNi nanoisland layers, the Drude dc conductivity drops well below the MIR limit (see Table 1) and the low-energy band at 2 eV becomes essentially suppressed, while the pronounced increase in the higher-energy band around 6-8 eV is observed (see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another paradigm is represented by the MLF sample N1, where the 0.52-nm thick FeNi layer is far from the percolation transition and the FeNi layers are well separated from each other (by 4.6 nm). Earlier, we established that ultrathin monolayers of FeNi nanoislands exhibit superparamagnetic-like (SPM) behaviour at room temperature, associated with their giant magnetic moments of 10 3 -10 5 µ B 36,40 . In the MLF sample N1, incorporating www.nature.com/scientificreports/ www.nature.com/scientificreports/ such FeNi nanoisland layers, the Drude dc conductivity drops well below the MIR limit (see Table 1) and the low-energy band at 2 eV becomes essentially suppressed, while the pronounced increase in the higher-energy band around 6-8 eV is observed (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Near the percolation transition within the FeNi layers strong magnetic dipole-dipole and exchange interactions between the FM nanoislands become relevant. It was shown that in quasi-2D systems of FM nanoparticles collective superferromagnetic (SFM) states can exist in their self-assembled local arrangements (clusters) at comparatively high temperatures 36,39,40 . We suppose that in here GMR-like case is realized, where the interlayer coupling between two neighboring FeNi layers is driven by the indirect exchange interactions via the itinerant charge carriers of the Ta spacer layer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1). Here with increasing the FeNi layer thickness across the percolation threshold the evolution from superparamagnetic (SPM) through superferromagnetic (SFM) to ferromagnetic (FM) behaviour within the FeNi layer [29][30][31] will modify the strength of the indirect exchange interaction in ensembles of magnetic FeNi nanoislands. This, in turn, will strongly influence the itinerant charge carriers of the Ta layer, promoting conditions for their enhanced localisation or delocalisation, leading to the appearance or disappearance of electronic "puddles".…”
mentioning
confidence: 99%